PERANCANGAN KONFIGURASI STRUKTUR TOWER DAN PEMBUATAN BILAH KOMPOSIT (SANDWICH) UNTUK APLIKASI TURBIN ANGIN - Hendrix Noviyanto Firmansyah; Mohammad Ardi Cahyono (Institut Teknologi Dirgantara Adisutjipto, 2016)
Tower is a structure vertically designed that the blades and other components attached. The process for structural design for the tower starts by identifying all of the requirements, and then specifies the desired design criteria. The desired design criteria are high strength, low cost, lightweight, does not require a large area, ease of assembly and transport. The proposed tower types are guyed, lattice, and tubular. The analysis result shows that the lattice tower type matches with the design criteria. The next processes are modeling and stress analyzing using MSC Patran/Nastran. The maximum stress is 42 Newton per milimeters square and the Margin of safety (MS) value is 7.815, so the structure is safe. In the process of making the composite sandwich wind blades, it is starts with the creation of the master molding, mold, foam cores and assembly. The results of the three blades were made indicate by a difference in weight. It is caused by the manufacturing system (manual). However, the difference is still relevant or good because it is less than 5 percent.